A DPIM-based framework for reliability analysis of building structures under stochastic near-fault ground motions - ICASP14; Chen, Guohai; Yang, Dixiong (My University, 2023)
Near-fault ground motions have the forward directivity effect and fling-step effect, both of which can produce the distinct long-period pulse in velocity time histories. Such velocity pulses with larger amplitude easily result in the nonlinear seismic responses and severe damage to building structures. Generally, earthquake ground motions also possess strong randomness and nonstationary characteristic. Therefore, the stochastic generation model of near-fault ground motions and the reliability assessment of structures play crucial roles in performance-based earthquake engineering. This study proposes the stochastic synthesis model of nonstationary near-fault ground motion and the efficient method for assessing first-passage dynamic reliability for structures. Firstly, the stochastic model for generating stationary near-fault pulse-like ground motions is established. In the model, the velocity time history with the strongest pulse is generated based on the orthogonal horizontal components by using wavelet analysis. The nonstationary model is suggested to synthesize the high-frequency residual acceleration time history. Secondly, the probability density integral equation (PDIE) controlling the propagation of randomness from stochastic ground motions to structural responses is derived based on the principle of probability conservation. By using the techniques of partition of probability space and smoothing of Dirac delta function, the direct probability integral method (DPIM) is proposed to efficiently solve PDIE and obtain the probability density functions of stochastic responses of structures. Moreover, the DPIM is extended to assess the first-passage dynamic reliability of building structures with nonlinear hysteretic behaviour. Finally, the effectiveness of established stochastic model and efficiency of proposed DPIM for seismic reliability assessment for hysteretic frame structure in near-fault area are demonstrated by numerical examples. Additionally, the effect of the velocity pulse on the failure probability of building structures is also scrutinized.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED